초음파 주파수 및 반응조건 변화에 따른 나프탈렌 분해효율과 OH 라디칼의 발생량 비교 - 박종성(Jong Sung Park); 박소영(So Young Park); 오재일(Jei Ll Oh); 정상조(Sang Jo Jeong); 이민주(Min Ju Lee); 허남국(Nam Guk Her) (Daehan hwan'gyeong gonghag hoeji, 2009)
Naphthalene is a volatile, hydrophobic, and possibly carcinogenic compound that is known to have a severe detrimental effect to aquatic ecosystem. Our research examined the effects of various operating conditions (temperature, pH, initial concentration, and frequency and type of ultrasound) on the sonochemical degradation of naphthalene and OH radical production. The MDL (Method detection limit) determined by LC/FLD (1200 series, Agilient) using C-18 reversed column is measured up to 0.01 ppm. Naphthalene vapor produced from ultrasound irradiation was detected under 0.05 ppm. Comparison of naphthalene sonodegradion efficiency tested under open and closed reactor cover fell within less than 1% of difference. Increasing the reaction temperature from $15^{°}C$ to $40^{°}C$ resulted in reduction of naphthalene degradation efficiency ($15^{°}C$: 95% ${→}$ $40^{°}C$: 85%), and altering pH from 12 to 3 increased the effect (pH 12: 84% ${→}$pH 3: 95.6%). Pseudo first-order constants ($k_1$) of sonodegradation of naphthalene decreased as initial concentration of naphthalene increased (2.5 ppm: $27.3{×}10^{-3}\;min^{-3}\;{→}$ 10 ppm : $19.3{×}10^{-3}\;min^{-3}$). Degradation efficiency of 2.5 ppm of naphthalene subjected to 28 kHz of ultrasonic irradiation was found to be 1.46 times as much as when exposed under 132 kHz (132 kHz: 56%, 28 kHz: 82.7%). Additionally, its $k_1$ constant was increased by 2.3 times (132 kHz: $2.4{×}10^{-3}\;min^{-1}$, 28 kHz: $5.0{×}10^{-3}\;min^{-1}$). $H_2O_2$ concentration measured 10 minutes after the exposure to 132 kHz of ultrasound, when compared with the measurement under frequency of 28 kHz, was 7.2 times as much. The concentration measured after 90 minutes, however, showed the difference of only 10%. (concentration of $H_2O_2$ under 28 kHz being 1.1 times greater than that under 132 kHz.) The $H_2O_2$ concentration resulting from 2.5 ppm naphthalene after 90 minutes of sonication at 24 kHz and 132 kHz were lower by 0.05 and 0.1 ppm, respectively, than the concentration measured from the irradiated M.Q. water (no naphthalene added.) Degradation efficiency of horn type (24 kHz) and bath type (28 kHz) ultrasound was found to be 87% and 82.7%, respectively, and $k_1$ was calculated into $22.8{×}10^{-3}\;min^{-1}$ and $18.7{×}10^{-3}\;min^{-1}$ respectively. Using the multi- frequency and mixed type of ultrasound system (28 kHz bath type + 24 kHz horn type) simultaneously resulted in combined efficiency of 88.1%, while $H_2O_2$ concentration increased 3.5 times (28 kHz + 24 kHz: 2.37 ppm, 24 kHz: 0.7 ppm.) Therefore, the multi-frequency and mixed type of ultrasound system procedure might be most effectively used for removing the substances that are easily oxidized by the OH radical. 나프탈렌은 휘발성이 있는 소수성 물질로 발암유발 가능성이 있고, 수생태계에 심각한 영향을 미친다. 본 연구는 초음파의 주파수 및 반응조건별 나프탈렌 분해효율과 OH 라디칼 변화량을 조사하였다. C-18 역상칼럼을 이용한 LC/FLD (1200 series, Agilent)로 나프탈렌을 분석한 결과 MDL (Method detection limit)은 0.01 ppm이었다. 초음파 조사동안 휘발된 나프탈렌은 거의 검출되지 않았고(0.05 ppm 이하), 반응조 덮개 개폐별 나프탈렌 분해효율은 거의 차이를 보이지 않았다(1% 이내). 초음파 반응온도가 증가할수록 나프탈렌 제거효율은 감소하는 경향($15^{°}C$: 95% ${→}$ $40^{°}C$: 85%)을 보였고, pH가 낮을수록 나프탈렌 분해효율이 증가(pH 12: 84% ${→}$ pH 3: 95.6%)하였다. 나프탈렌 초기농도의 감소에 따라 반응속도는 증가하는 경향을 보여주었다(2.5 ppm: $27.3{×}10^{-3}\;min^{-1}$, 5 ppm: $27.3{×}10^{-3}\;min^{-1}$, 10 ppm : $19.0{×}10^{-3}\;min^{-1}$). 동일한 초음파 조건(2.5 ppm 나프탈렌, 0.075 W/mL, $20^{°}C$, pH 6.8)에서 28 kHz의 분해효율이 132 kHz보다 약 1.46배 높았고(132 kHz: 56%, 28 kHz: 82.7%), 유사 일차반응 속도상수($k_1$)도 약 2.3배 높게 나타났다(132 kHz: $2.4{×}10^{-3}\;min^{-1}$, 28 kHz: $5.0{×}10^{-3}\;min^{-1}$). 초음파 조사 10분 후 $H_2O_2$ 농도는 132 kHz가 28 kHz보다 약 7.2배 높았지만(132 kHz: 0.36 ppm, 28 kHz: 0.05 ppm), 조사 90분 후에는 28 kHz가 132 kHz보다 1.1배 높았다(28 kHz: 0.45 ppm, 132 kHz: 0.4 ppm). 2.5 ppm 나프탈렌 용액에 132 kHz와 28 kHz 초음파 조사시 발생된 $H_2O_2$ 농도는 초순수에 초음파 조사한 결과보다 각각 0.1 ppm과 0.05 ppm씩 낮게 나타났다. 혼형(24 kHz)과 배스형(28 kHz) 초음파의 나프탈렌 분해효율은 각각 87%와 82.7%였고, $k_1$은 $22.8{×}10^{-3}\;min^{-1}$와 $18.7{×}10^{-3}\;min^{-1}$로 산출되었다. 다주파 복합형 초음파 시스템(28 kHz 배스형 + 24 kHz 혼형 초음파)의 나프탈렌 분해효율은 단일주파수 24 kHz(혼형)와 비슷한 제거효율을 보였으나(88%), $H_2O_2$의 농도는 약 3.5배 높게 조사되었다(28 kHz + 24 kHz: 2.37 ppm, 24 kHz: 0.7 ppm). 이와 같은 다주파 복합형 초음파 시스템은 OH 라디칼에 의해 산화가 잘 일어나는 물질의 분해에 매우 효과적으로 적용될 수 있을 것으로 예상된다.